Philosophy of history of Descartes’ philosophy - Bęben, Dariusz (Folia Philosophica, 2010)
Review of Milovan Ješič's book "Descartes' Metamorphoses in the Philosophical Reception of Hegel, Husserl, and Heidegger," Prešov: Rokus Publishing House, 2006.